Medium-chain triglycerides tricaprin TC10 and tricaprylin TC8 attenuated HFD-induced cognitive decline in a manner dependent on or independent of GLP-1 - Maiko Shobako; Kohei Kawano; Eriko Taniguchi; Kousaku Ohinata (Scientific Reports)
Abstract Population aging is the most important social and medical demographic issue worldwide; therefore, healthy aging is important. The increasing prevalence of dementia and cognitive decline are major health concerns. Medium-chain triglycerides (MCTs) have been shown to improve cognitive decline. The present study investigated the effects and mechanisms of action of orally administered MCTs, including tricaprylin (TC8), tricaprin (TC10), and trilaurin (TC12), on cognitive function in mice fed a high-fat diet (HFD). The administration of TC8 and TC10 attenuated cognitive decline. A relationship has been reported between cognitive dysfunction and impaired glucose metabolism. The administration of TC8 and TC10 also reduced blood glucose levels in the glucose tolerance test. Cognitive improvements by MCTs are widely attributed to the ketogenic effect. In the present study, TC8 significantly increased blood ketone concentrations, whereas TC10 did not. On the other hand, TC10 increased the plasma concentration of glucagon-like peptide-1 (GLP-1), the hormone that promotes insulin secretion. The administration of the GLP-1 receptor antagonist, exendin(9–39), blocked the cognitive-enhancing effects of TC10. These results suggest that TC10 improved cognitive function via the GLP-1 receptor. The in vitro experiment indicated that 2-monocaprin (2-MC10), not TC10, stimulated the secretion of GLP-1 and decreased intracellular cAMP concentrations. In conclusion, we herein demonstrated that TC8 and TC10 attenuated cognitive decline through different mechanisms. This is the first study to suggest that TC10 attenuates cognitive decline via GLP-1.